Remodelling of supernumerary leaflet primordia leads to bicuspid aortic valve caused by loss of primary cilia - Alqahtani, Ahlam; Eley, Lorraine; Newton, Jake; McDonald, Kimberley; Connolly, Chloe; Rodrigues-Cleto, Cindy; Neffeova, Kristyna; Lopez, Leonor; Arias, Javier; Derrick, Christopher J; Alaradi, Mashael; Kolesova, Hana; et al. (Cardiovascular research, 2025)
AIMS: Bicuspid aortic valve (BAV), where two valve leaflets are found instead of the usual three, affects 1-2% of the general population and is associated with significant morbidity and mortality. Despite its frequency, the majority of cases remain unexplained. This is, at least in part, because there are two types of valve leaflet primordia: endocardial cushions and intercalated valve swellings (ICVS). Moreover, multiple progenitors make distinct contributions to the formation of these primordia. Genomic studies in mouse and human have suggested a correlation between BAV and malfunctional primary cilia. However, the precise requirement for cilia during early embryonic valvulogenesis remains unknown. METHODS AND RESULTS: Here, we disrupted primary cilia by deleting the ciliary gene Ift88 in the main progenitor cells forming the aortic valve using specific Cre drivers: Wnt1-Cre for neural crest cells, Isl1-Cre for second heart field (SHF) cells, Tie2-Cre for endocardial-derived cells, and Tnnt2-Cre for direct-differentiating SHF in the ICVS. Loss of Ift88, and thus primary cilia, from neural crest cells and endocardium did not impact aortic valve formation. However, primary cilia were essential in SHF cells for aortic valve leaflet formation, with over half of Ift88f/f;Isl1-Cre mutants presenting with BAV. As the valve leaflets were forming, 50% of the Ift88f/f;Isl1-Cre mutants had two small leaflets in the position of the usual posterior leaflet, meaning that at this stage, the aortic valve was quadricuspid, which then remodelled to BAV by E15.5. Mechanistic studies demonstrated premature differentiation of SHF cells as the ICVS formed, leading to the formation of a broadened ICVS that formed two posterior leaflet precursors. This abnormality in the formation of the ICVS was associated with disruption of Notch-Jag1 signalling pathway, with Jag1f/f;Isl1-Cre mutants presenting with a similar phenotype. CONCLUSION: These data show that primary cilia, via the Notch-Jag1 signalling pathway, regulate differentiation of SHF cells in the aortic valve primordia. Additionally, we identify a mechanistic link between the developmental basis of quadricuspid and bicuspid arterial valve leaflets.
Keywords: Tumor Suppressor Proteins; buněčná diferenciace; nemoci srdečních chlopní; bikuspidální aortální chlopeň; Aortic valve; crista neuralis; Signal Transduction; vývojová regulace genové exprese; Mice, Transgenic; Cell Differentiation; Ift88; Receptors, Notch; Wnt1 Protein; nádorové supresorové proteiny; fenotyp; intercalated valve swelling; aortální chlopeň; second heart field; protein Wnt1; modely nemocí na zvířatech; Gene Expression Regulation, Developmental; Aortic Valve; endokardové polštáře; Phenotype; Cilia; signální transdukce; myši transgenní; receptory Notch; Animals; zvířata; Mice, Knockout; Neural Crest; Bicuspid Aortic Valve Disease; bicuspid aortic valve; Disease Models, Animal; Endocardial Cushions; cilie; Heart Valve Diseases; myši knockoutované